Development Media Learning Audio Visual Based on Web Blog for Increasing Economy Learning Result - Alfis Aldera; Arwansyah Arwansyah; Fitrawaty Fitrawaty (RIRAI Publisher, 2024)
Media is one component that is really needed in learning. Teachers as facilitators in learning are required to be able to provide learning media that is suitable for use in learning. However, based on the results of field observations, it was found that there was still a lack of use of learning media in the learning process. The aim of this research is to develop and implement Web Blog-based audio- visual economics learning media to improve learning outcomes in the Taxation economics subject for class XI IPS students at SMA Negeri 1 Takengon. This research is development research (R&D) using the Four-D (4D) method. This research was conducted at SMA Negeri 1 Takengon, with a population of class XI IPS. The results of this research are based on assessments carried out by validation experts and user responses, an average assessment percentage of 93.70% was obtained in the